If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -1(w + 6) Reorder the terms: 1 = -1(6 + w) 1 = (6 * -1 + w * -1) 1 = (-6 + -1w) Solving 1 = -6 + -1w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add 'w' to each side of the equation. 1 + w = -6 + -1w + w Combine like terms: -1w + w = 0 1 + w = -6 + 0 1 + w = -6 Add '-1' to each side of the equation. 1 + -1 + w = -6 + -1 Combine like terms: 1 + -1 = 0 0 + w = -6 + -1 w = -6 + -1 Combine like terms: -6 + -1 = -7 w = -7 Simplifying w = -7
| 2x^3+x+20=2 | | -6n=-78 | | 2x+56=7x-14 | | m+m+3=27 | | 3(n+4)=8+n | | x^3-4x^2-1=0 | | x^3-x^2+x-6=0 | | 4x+-7=3+2x | | 190-2x=34x+18 | | 4x+-7= | | x^3+2x^2-x+1=0 | | -7(3+4x)= | | 10+6x=-x+10 | | 2x+37=6x-7 | | 2x+1=-4 | | 2x+5=5x-16 | | 9p^2r-73pr-70r=0 | | -.75x=-6 | | r+19=27 | | 4a+8b+11a-10b= | | 5x-1-4x=1x+7 | | 3(7x+6y)=6x | | 3+6x=x-7 | | 2(x+3)+4x=6x+6 | | 6y=8+-9+6y | | 23=11+n | | 4x-6(2x+8)= | | n+2.4=-6.5 | | 0.5(2x-2)=5x+4 | | 4x+7y=71 | | x^2=8100 | | 4x-3x-5=x |